Analisis Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan Pasca Pademik Covid-19 - Ary Prasetyo; Suratman Suratman; Asih Purwana Sari; Daris Purba (Manivest : Jurnal Manajemen, Ekonomi, Kewirausahaan, dan Investasi, 2023)
After the Covid-19 pandemic, the implementation of health protocols began to be relaxed so that employee motivation and work discipline also began to be questioned. The aim of this research is to determine the influence of work motivation and work discipline on employee performance after the Covid-19 pandemic. The research method used by researchers is quantitative research with the type of field research, data collection using instruments in the form of questionnaires and sampling using simple random sampling. The population in this study was 790 people and the sample taken was 266 respondents. The data processing technique uses Structural Equation Model (SEM) with AMOS version 24 software. The results of this research show that work motivation has a direct positive and significant effect on employee performance and work discipline has a direct positive and significant effect on employee performance after the Covid-19 pandemic. The direct influence of work motivation and work discipline on employee performance after the Covid-19 pandemic is 41.8%. Keywords:Covid-19, Work Motivation, Work Discipline, Employee Performance, AMOS